2014
DOI: 10.3109/14764172.2013.854626
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fractional, nonablative, 1550-nm laser and 595-nm pulsed dye laser for the treatment of facial erythema resulting from acne: A split-face, evaluator-blinded, randomized pilot study

Abstract: Both lasers are effective and safe modalities for the treatment of acne erythema; however, these data suggest better clinical efficacy with the use of a 1550-nm, erbium-glass fractional laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(85 citation statements)
references
References 11 publications
1
79
0
5
Order By: Relevance
“…The effectiveness was assessed on the basis of a mean change in investigator's and patients' clinical evaluation and mexameter scores. QY Park et al suggested that physicians preferred the non‐ablative 1,550‐nm fractional laser for the treatment of acne erythema (Park, Ko, Seo, & Hong, ). Wang B et al found that the IPL treatment reduced skin redness by about 10% and skin pigmentation by about 17%.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness was assessed on the basis of a mean change in investigator's and patients' clinical evaluation and mexameter scores. QY Park et al suggested that physicians preferred the non‐ablative 1,550‐nm fractional laser for the treatment of acne erythema (Park, Ko, Seo, & Hong, ). Wang B et al found that the IPL treatment reduced skin redness by about 10% and skin pigmentation by about 17%.…”
Section: Discussionmentioning
confidence: 99%
“…One patient developed a purpuric eruption that lasted 2 days. There was no association found between skin type and treatment efficacy or side effects [39].…”
Section: Nm Pulse Dye Lasermentioning
confidence: 84%
“…The mean improvement score on a quartile‐grading scheme was 3.42 for PDL, versus 3.33 for the 1550 nm fractional laser. However, patients tended to report a better experience with the fractional system, as 91.7% versus 75.0% of patients rated the results as “good” or “excellent” .…”
Section: Traditional Non‐ablative Lasersmentioning
confidence: 98%
See 1 more Smart Citation
“…[3][4][5][6][7][8] Fractional photothermolysis was first introduced by Manstein et al 9 The Sellas laser used in this study is a non-ablative fractional laser, which is a mid-infrared wavelength emitted by a 1550-nm, erbium-glass laser. 10 It creates microscopic non-contiguous columns of thermal injury to make unique damage patterns called microthermal treatment zones (MTZ). 10 Since the tissue surrounding each MTZ were spared, fractional photothermolysis allows re-epithelialization and remodelling of the dermal collagen.…”
mentioning
confidence: 99%